A multi-objective vibrating particle system algorithm for data clustering - Kaur, Arvinder; Kumar, Yugal (Pattern analysis and applications : PAA, 2022)
Clustering is an important data mining technique described as unsupervised learning. Till date, many single-objective clustering algorithms have been developed on the basis of swarm intelligence and evolutionary techniques. It is noticed that these clustering algorithms provide better solutions for clustering problems, but sometimes, these solutions seem to be biased and also not appropriate for the problem with geometrical shapes datasets. In turn, performance of the clustering algorithms can be degraded. One of the possible solutions is to adopt multi-objective approach instead of single objective. In multi-objective approach, more than one objective functions can be considered for solving the clustering problems and these functions are conflicted in nature. Further, in multi-objective approach, Pareto-optimal solutions can be generated for improving the clustering performance. Hence, this paper presents a multi-objective clustering algorithm based on vibrating particle system (VPS) for effective cluster analysis, called MOVPS. This work considers intra-cluster variance and connectedness as objective functions, and VPS algorithm is used for optimizing the aforementioned objectives to obtain good clustering results. The performance of MOVPS algorithm is tested over a set of benchmark datasets and validated by comparing clustering results with various multi-objective and single-objective clustering algorithms from the literature. The simulation results illustrate the effectiveness of the MOVPS algorithm based on F -measure, coverage, distribution, convergence, non-dominating vector generation and intra-cluster distance measures. The simulation results showed that the proposed MOVPS algorithm enhances the clustering results significantly in comparison with existing multi-objective and single-objective clustering algorithms.